Evaluating Transportation Land Use Impacts. Considering the Impacts, Benefits and Costs of Different Land Use Development Patterns. - Litman, Todd (My University, 2019)
This report examines ways that transportation decisions affect land use patterns, and the resulting economic, social and environmental impacts. These include direct impacts on land used for transportation facilities, and indirect impacts caused by changes to land use development patterns. In particular, certain transportation planning decisions tend to increase sprawl (dispersed, urban-fringe, automobile-dependent development), while others support smart growth (more compact, infill, multi-modal development). These development patterns have various economic, social and environmental impacts. This report describes specific methods for evaluating these impacts in transport planning.
Keywords: Verkehrsentwicklungsplanung; Auswirkung; Flächennutzung; Landnutzung; Zersiedelung; Infrastrukturplanung; Siedlungswachstum; Kosten-Nutzen-Analyse; Smart growth